Legal Protection in the Settlement of Wage Disputes for Workers through the Concept of Restorative Justice - Muhammad Iredenta Tania; Yuhelson Yuhelson; Dodi Sugianto (Budapest International Research and Critics University, 2022)
The legal bond between employees and the self-employed begins with the making of a good activity agreement made by recording or by means of words. The contract which is charged with rights and roles thereafter in its application often arises problems, which if there is no one-on-one interpretation or no misunderstanding and if it cannot be resolved the conclusions may end in apparent clashes between the parties. Clashes or clashes can also be established in the labor environment where it relates to parties who are said to be workers and self-employed. Indeed, clashes or clashes between workers and self-employed people do not need to be worried because clashes can have positive consequences for the parties participating if the clashes are not based on enthusiastic violence. If the clashes are based on violence, they will bring about loss and conflict. So far, clashes between workers and the self-employed have often been resolved in insurgent ways such as violent protests, arson, strikes and industrial closures. The clashes should be resolved in harmony and profitability. Sourced from Article 86 of Law Number. 13 of 2003 concerning Manpower says: a. Every worker or employee has the right to get protection for: 1) Security and Health Activities; 2) Morals and Decency; and 3) Treatment that matches the degree and degree of people and religious values. b. To prevent the safety of workers or employees to create maximum productivity of activities organized by security and health activities. c. Protection is also defined in Paragraph (1) and (2) is carried out in accordance with legal laws and regulations.